No : why kids--of all ages--need to hear it and ways parents can say it - Walsh, David Allen. frey50 (New York : Free Press, 2007)
It's not just a one-word answer, it's a parenting strategy. By saying No when you need to, you help your children develop self-reliance, self-discipline, respect, integrity, the ability to delay gratification, and a host of other crucial character traits they need. Although the importance of using No should be obvious, many parents have a hard time saying it--even when they know they should--when other parents and the culture around them are being permissive. Psychologist and parenting expert Walsh provides you with an arsenal of tactics, explanations, and examples for using No the right way with your kids. With Dr. Walsh's straightforward "parent tool kits," you can assess and improve your relationship with your kids, set and enforce limits that make sense for different ages (from toddlers to teens), and otherwise make No a positive influence on kids' behavior and in your overall family life.--From publisher description.
No: why kids need it -- Saying No in a yes culture -- No and the brain -- Self-esteem: kids need the real thing -- Styles of parenting -- A baby's first year: a time to connect -- Toddlers and preschoolers: limits and consequences -- Catching kids being good: the middle years -- The teenage years: loosen but don't let go -- Wired differently: special-needs children and No -- Practical questions about No -- Taming the gimmes -- Raising mediawise kids -- No is not a destination: No is the road to Yes.
Keywords: Child rearing; Parenting; Parent and child; Character